Association Between Cardiovascular Risk Factors and CAD Severity by CAD-RADS Categories and Comprehensive CTA Score - Raharjo, Pradana Pratomo; Purnomowati, Augustine; Kusumawardhani, Nuraini Yasmin; Astuti, Astri; Achmad, Chaerul; Pramudyo, Miftah; Karwiky, Giky; Akbar, Mohammad Rizki (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Coronary artery disease (CAD) is the leading cause of mortality and morbidity worldwide, including in Indonesia. Risk factors (RFs) play an important role in both pathogenesis and management of cardiovascular (CV) diseases. Coronary computed tomography angiography (CTA) is a reliable non-invasive diagnostic method. Coronary Artery Disease Reporting and Data System (CAD-RADS) categories and comprehensive CTA score describes CAD severity on coronary CTA and provides additional prognostic value.Objective: To explore the link between traditional cardiovascular risk factors and CAD severity based on CAD-RADS and comprehensive CTA scores.Methods: This retrospective, single-center study was conducted at a tertiary hospital using data from the Cardiovascular Imaging Database of the hospital from January 2020 to June 2022. Data meeting the inclusion and exclusion criteria were analyzed using ordinal and binary regressions.Results: A total of 423 patients' data were analyzed. Ordinal regression revealed significant links between age ≥ 65 years, male gender, hypertension, diabetes, and higher CAD severity based on both CAD-RADS and comprehensive CTA scores. Binary regression showed that older age and male gender were independently associated with CAD-RADS ≥ 3 and comprehensive CTA score ≥ 6. Diabetes was linked to CAD-RADS ≥ 3, and hypertension was tied to a comprehensive CTA score ≥ 6. The number of risk factors showed a trend toward CAD severity (p=0.069) and a significant link with comprehensive CTA score (p=0.012).Conclusion: There is a significant association between traditional cardiovascular risk factors and CAD severity as quantified by both CAD-RADS and comprehensive CTA score.